#327 : The Characteristics of Menopausal Women in Moewardi Hospital: What Factors Could Lead to the Depression? - Abida Zuhra Jatiningtyas; Christa Edo Nugroho; Agung Sari Wijayanti; Uki Retno Budihastuti; Eriana Melinawati (Fertility & Reproduction, 2023)
Background and Aims: A Woman may begin to experience several symptoms during the premenopausal and menopausal stages, including depression. Some studies have linked the emergence of various symptoms, including emotional changes, to hormonal changes. Several factors could lead to depression, such as the knowledge and the behaviour of premenopausal and menopausal women, nutritional status, duration of menopause, access to health care, and many more. The primary goal of this study was to determine the relationship between menopause and depression by examining the subjects’ Hamilton Depression Rating Scale (HAM-D) results and some potentially related characteristics. Method: This research was held in Moewardi Hospital, Surakarta, Indonesia between July until December 2022, involving participants women aged 40-60 years old, totaling 60 people. Thematic analysis of semi-structured interviews based on the HAM-D was employed in this study. We examined the characteristics such as age, duration of menopause, body mass index, hypertension, anxiety, and activities. The data were collected from women aged 40 and over, in the premenopausal or menopausal phase, who agreed to be interviewed and gave informed consent and analysed with IBM SPSS Statistic 23. Results: Statistical tests showed that there was no correlation between depression and a woman’s age (p=0.404), duration of menopause (p=0.846), body mass index (p=0.339), and hypertension (p=0.909). We found significant results of depression with anxiety (p<0.001) as well as patients’ activities (p<0.001). These two characteristics were included in the HAM-D and then grouped into five categories according to the HAM-D. This questionnaire gave results weak correlation between depression and the menopausal phase (p=0.176). Conclusion: Several factors could lead to the incidence of depression in premenopausal and menopausal women. This study found that there was a correlation between depression and anxiety and patient’s activity.